Botanical Garden including information on their physical and mechanical properties, natural durability, distribution, prospect and other supporting data; (2) to analyze the lesser-known wood species that could be used for construction materials and then recommend them to be developed through Industrials Plantation Forest. The steps of the study were first collection of data on timber species from herbarium catalogue; second collection of data on the properties of wood from various sour - Ika WAHYUNI; Wahyu DWIANTO; Yusup AMIN; Teguh DARMAWAN (Jurnal Ilmu dan Teknologi Hasil Hutan, 2008)
Botanical Garden including information on their physical  and   mechanical  properties,   natural  durability,   distribution, prospect and other supporting data; (2) to analyze the lesser-known wood species that could be used for  construction materials and then recommend them to be developed through Industrials Plantation Forest. The steps of the study were first collection of data on timber species from herbarium catalogue; second collection of data on the properties of wood from various sources; third, observation of stem morphology in the field. The result of the catalogue study showed that there were 291 timber tree species grown in Cibodas Botanical Garden which were comprised of 14 major commercial timbers, 74 minor commercial timbers, and 142 lesser known timbers. These timber species were also distributed in other parts of Indonesia. Observation in the field then generated 49 lesser-known wood species that could be used for construction materials based on their stem form and branch height. From the reference and catalogue study, it was found that there were 14 wood species belongs to strength class I to III with natural durability ranges from very durable to moderate. These woods were then evaluated based on their morphological features and prospects. Finally, it was found that only ten wood species that were suitable to be used for construction materials, i.e. Acmena acuminatissima (Blume.) Merr. & Perry (Kelat); Adenanthera microsperma Teijsm. & Binn. (Saga); Baccaurea parviflora (Muell. Arg.) (Setambun); Casuarina junghuhniana Miq. (Cemara Gunung); Garcinia parvifolia and G. beccari (Manggis Hutan); Gymnostoma sumatranum (Joogb. ex de Vriese) L.A.S. Johnson (Cemara Sumatra); Mimusops elengi L. (Tanjung); Neonauclea lanceolata and N. obtusa (Ki Anggrit). However, the result of this study needs to be supported by further study on their wood properties since the present data were mostly qualitatives. Further research concerning their silviculture, growth rate, and susceptibility to the diseases were also needed to be done.   Keywords : Lesser-known timbers, Cibodas Botanical Garden.